Integrated Multichip Analysis Identifies Potential Key Genes in the Pathogenesis of Nonalcoholic Steatohepatitis - Ye, Jianzhong; Lin, Yishuai; Wang, Qing; Li, Yating; Zhao, Yajie; Chen, Lijiang; Wu, Qing; Xu, Chunquan; Zhou, Cui; Sun, Yao; Ye, Wanchun; Bai, Fumao; et al. (Frontiers in Endocrinology, 2020)
Background: Nonalcoholic steatohepatitis (NASH) is increasingly developing into a major chronic liver disease worldwide. However, little is known about the pathogenesis and progression mechanism of NASH. Our aim was to identify key genes and their potential molecular functions involved in the development from hepatic steatosis to NASH. Methods: Gene expression datasets that concomitantly contain NASH patients, hepatic steatosis patients and healthy subjects were download from the Gene Expression Omnibus database using R studio with biobase and GEOquery packages. Differentially expressed genes (DEGs) were then identified using the R limma package. Functional annotation and enrichment analysis of DEGs were conducted using R package ClusterProfile, and the protein-protein interaction (PPI) network was constructed using STRING database. Results: In this study, microarray data GSE48452, GSE63067 and GSE89632 were selected, including 45 NASH patients, 31 hepatic steatosis patients and 43 healthy subjects. A total of 26 DEGs (2 up-regulated and 24 down-regulated) were found in NASH patients vs. healthy controls that were commonly shared with steatosis subjects vs. healthy controls, among which the most significant DEGs were FOSB (P = 3.43×10-15), followed by CYP7A1 (P = 2.87×10-11), and FOS (P = 6.26×10-11). Proximal promoter DNA-binding transcription activator activity, RNA polymerase II-specific (P = 1.30×10-5) was the most significantly enriched for molecular function terms in gene ontology analysis. KEGG pathway enrichment analysis showed that MAPK signaling pathway (P = 3.11×10-4) was significantly enriched. Conclusion: This study characterized hub genes of liver transcriptome which may contribute to NASH progression developed from hepatic steatosis.